2012
DOI: 10.1002/hyp.9574
|View full text |Cite
|
Sign up to set email alerts
|

Snow accumulation and ablation response to changes in forest structure and snow surface albedo after attack by mountain pine beetle

Abstract: This study quantified changes in snow accumulation and ablation with forest defoliation in a young pine stand attacked by mountain pine beetle, a mature mixed species stand, and a clearcut in south‐central British Columbia. From 2006 to 2012, as trees in the pine stand turned from green to grey, average canopy transmittance increased from 27% to 49%. In the mixed stand, transmittance remained constant at 19%. In 2009, the year of greatest needle loss, average snow surface litter cover in the pine stand was 29%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…Over the basin, the results showed that FGE was reduced in late June 2013; an early June flood would have generated larger volume (+15%), and an early May flood would have generated higher peak discharge (+13%). Although the results showed that 'hotspots' such as forest clearings could generate more runoff in spring leading to higher flood water yields with greater cleared area, consistent with modelling forest removal effects on peak flow in spring , heavy rainfall events in May have been relatively rare so far in the region (Harder et al, 2015;Liu et al, 2016;Whitfield and Pomeroy, 2016). This helps to explain why forest management practices such as clear-cutting caused small or no impact on peak streamflow or timing at Marmot Creek (Harder et al, 2015;Neill, 1980).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Over the basin, the results showed that FGE was reduced in late June 2013; an early June flood would have generated larger volume (+15%), and an early May flood would have generated higher peak discharge (+13%). Although the results showed that 'hotspots' such as forest clearings could generate more runoff in spring leading to higher flood water yields with greater cleared area, consistent with modelling forest removal effects on peak flow in spring , heavy rainfall events in May have been relatively rare so far in the region (Harder et al, 2015;Liu et al, 2016;Whitfield and Pomeroy, 2016). This helps to explain why forest management practices such as clear-cutting caused small or no impact on peak streamflow or timing at Marmot Creek (Harder et al, 2015;Neill, 1980).…”
Section: Discussionsupporting
confidence: 61%
“…The results from flood simulations of changing forest canopy and soil moisture storage capacity show that removing all forest canopy alone had minimal impacts on peak flood discharge and flow volume. This simulation might be similar to impacts of forest disease or low intensity wildfire (Fauria and Johnson, , ; Whitfield and Pomeroy, ; Winkler et al, ), and the results are very different from an examination of peak flow change with forest cover removal when peak flows are because of spring snowmelt (Pomeroy et al, ). The difference between this forest rainfall–runoff event and a snowmelt event is most likely because of the flood precipitation being two orders of magnitude greater than typical canopy interception storage capacities and the rainfall–runoff mechanisms that were dominant in the forested ecozones which differ from the snowmelt runoff mechanisms examined by Pomeroy et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Even as the ESMs project increasing precipitation and temperature, we see the variability in responses through the cascade of scale and land cover variability. This finding is consistent with other studies that observed that variability (forest cover composition and topography) in the area and size of forest-shrub conversion can buffer responses of streamflow or evapotranspiration shifts from climate change (Winkler et al, 2014;Caldwell et al, 2016).…”
Section: Changing Streamflow and Water Balancessupporting
confidence: 93%
“…Mean annual temperature is 3.3°C, with mean monthly temperatures ranging from À7.1°C in December to 13.9°C in July. The Köppen climate classification for the region is Dfc (sub-arctic) while the provincial Biogeoclimatic Ecosystem Classification designation (BC Ministry of Forests and Range, 2008) is Montane Spruce dry mild variant (Winkler et al, 2014).…”
Section: Study Areamentioning
confidence: 99%